2012
DOI: 10.1111/j.1365-3083.2012.02699.x
|View full text |Cite
|
Sign up to set email alerts
|

IgG Subclasses Against Helicobacter pylori Isolates: An important Tool for Disease Characterization

Abstract: Helicobacter pylori infects around 50% of the world’s population and is associated with diverse pathologies. In the most severe cases, the bacterium causes peptic ulcers and gastric cancer. The interplay between H. pylori and the host’s immune response may help to determine the specific outcome of the infection. To study the relationship between antibody subclasses and variation in immune recognition, we determined the immunoglobulin G1 and 2 (IgG1 and IgG2) titres of sera obtained from patients with different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…21 Thus, DNA vaccination induces a shift from the Th1 to Th2 responses that fundamentally mimic the changing immune status in the host of GC with chronic H. pylori infection. 21,45 The elevated TNF-α level is identified after vaccination to mimic the changes in the TNF-α expression induced by H. pylori infection in patients with chronic gastritis, intestinal metaplasia, dysplasia and GC. 46 In addition, the H. pylori DNA vaccines stimulate significant proliferation of both peripheral CD3 + CD4 + and CD3 + CD8 + T cells in mice and the enhanced proliferation and effector roles of activated CD3 + T cells are thought to likely inhibit tumor growth and improve prognosis of Hp-GC.…”
Section: Discussionmentioning
confidence: 99%
“…21 Thus, DNA vaccination induces a shift from the Th1 to Th2 responses that fundamentally mimic the changing immune status in the host of GC with chronic H. pylori infection. 21,45 The elevated TNF-α level is identified after vaccination to mimic the changes in the TNF-α expression induced by H. pylori infection in patients with chronic gastritis, intestinal metaplasia, dysplasia and GC. 46 In addition, the H. pylori DNA vaccines stimulate significant proliferation of both peripheral CD3 + CD4 + and CD3 + CD8 + T cells in mice and the enhanced proliferation and effector roles of activated CD3 + T cells are thought to likely inhibit tumor growth and improve prognosis of Hp-GC.…”
Section: Discussionmentioning
confidence: 99%
“…The plates were then read using a microplate reader (GENios Plus, Tecan Austria GmbH, Grödig, Austria). The antibody titer was calculated by plotting luminescence versus serum dilution; the luminescence value was 1 above the background while the data were analysed by calculating the log10 of the titre dilution as described by Martinez-Becerra et al, [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the context of anti- H. pylori immunity, studies on serum anti -H. pylori IgG subclass have indicated that subjects with low levels of IgG2 anti- H. pylori antibody were at a risk of gastric cancer [13, 14], suggesting that a decreasing Th1 response is associated with developing gastric cancer. IL-10 inhibits the production of pro-inflammatory cytokines by inhibition of Th1 lymphocytes, and stimulation of B lymphocytes and Th2 lymphocytes and thus downregulates the inflammatory response [1517].…”
Section: Introductionmentioning
confidence: 99%